Implementation of Scientific Approach in Physics Learning in Makassar City - Andi Evi Sulfiyani Nurfathanah Amsal; Kaharuddin Arafah (Jurnal Pendidikan Fisika, 2020)
This research is a qualitative study that aims to uncover the implementation of scientific approaches and assessment systems in learning physics at senior high schools in Makassar. The research subjects consisted of 8 physics class XI teachers from 4 schools in Makassar City. The research data were obtained through questionnaires, documentation, observation, and interviews. Interviews aim to synchronize data obtained through questionnaires, observations and documentation. Based on the results of the study showed that, a scientific approach in learning physics by teachers has been implemented even though it has not been maximized. Likewise, authentic assessment in learning physics in aspects of knowledge and skills has been carried out well, but not yet in the attitude aspect. The cause of the lack of optimal is insufficient time, different abilities of students, the willingness of students to ask questions and seek help, responded accordingly, the number of learners is large, and the readiness is still inadequate.